Signaling value of top management team: Evidence from Chinese initial public offerings on US markets. Issue 3 (5th August 2019) - Amin, Muhammad; Wu, Jianfeng; Tu, Rungting
Abstract : Purpose: The purpose of this paper is to integrate the upper echelon theory with signaling theory and examine the impact of top management team (TMT) on the initial public offering (IPO) performance of Chinese firms in the USA. Design/methodology/approach: This study used Security Data Corporation (SDC) that is a central database for foreign IPOs in the USA. The authors identified 142 Chinese firms that issued stocks on the US markets between 2003 and 2014. This study used firm's final prospectuses to collect data manually. Findings: This study finds that the TMT characteristics such as functional heterogeneity and international exposure convey the positive signal of firm's legitimacy to the US investors and increase the IPO performance. Originality/value: This study extends the upper echelon perspective that has previously overlooked the signaling value of TMT characteristics in the foreign IPO studies. The top management plays an important role to the firm's successful foreign market listing. Since China joined the WTO in 2001, a large number of Chinese firms have started IPOs in the USA, but there is a dearth of research on these firms. This study aims to contribute to the study of international business and management and describes that the TMT functional heterogeneity and international exposure have a significant role in the success of Chinese foreign IPOs.